Asthma‐related outcomes associated with indoor air pollutants among schoolchildren from four informal settlements in two municipalities in the Western Cape Province of South Africa. (8th November 2018) - Olaniyan, Toyib; Dalvie, Mohamed Aqiel; Röösli, Martin; Naidoo, Rajen; Künzli, Nino; de Hoogh, Kees; Parker, Bhawoodien; Leaner, Joy; Jeebhay, Mohamed
Abstract: The health impact of indoor air pollution in informal settlement households has not been extensively studied in South Africa. This cross‐sectional study investigated the association between asthma and common indoor exposures among schoolchildren from four informal settlements located in two municipalities in the Western Cape Province. A total of 590 children, aged 9‐11 years, were recruited. The International Study of Asthma and Allergies in Childhood (ISAAC) questionnaire was administered to caregivers. Pulmonary function assessment included spirometry and fractional exhaled nitric oxide (FeNO). Phadiatop test for atopy was done. The prevalence of doctor‐diagnosed asthma was 3.4% (n = 20) among whom only 50% were on treatment. The prevalence of current wheeze was 12.9%, and 17.6% had airway obstruction (FEV1 < lower limit of normal), while 10.2% had airway inflammation (FeNO > 35 ppb). In adjusted logistic regression models, dampness, visible mold growth, paraffin use for cooking, and passive smoking were associated with a twofold to threefold increased risk in upper and lower airway outcomes. The strongest association was that of visible mold growth with rhinitis (adjusted odds ratio—aOR 3.37, 95% CI: 1.69‐6.71). Thus, there is a need for improved diagnosis of childhood asthma and Indoor Air Quality in informal settlement households.